Medical telerobotics and the remote ultrasonography paradigm over 4g wireless networks - Avgousti, Sotiris; Panayides, Andreas S.; Christoforou, Eftychios G.; Argyrou, Argyris; Jossif, Antonis; Masouras, Panicos; Novales, Cyril; Vieyres, Pierre (My University, 2018)
Medical telerobotic systems provide a framework for performing interventional and diagnostic procedures remotely utilizing communication networks. Over the past decade, various systems have demonstrated the feasibility and the significance of telerobotics, some of which have been already adopted in clinical practice. In this study, we elaborate on the potential and discuss associated challenges focusing on the enabling technologies, namely robotic manipulation, telecommunications, and vision systems. A case study of an end-to-end mobile teleechography software platform using the MELODY robotic system is presented, investigating the capability of commercially available 4G (and beyond) wireless networks to communicate clinically lossless medical video for remote diagnosis purposes. Performance analysis demonstrates that medical video transmission approaching the clinical standards of in-hospital examination while conforming to strict delay requirements is achievable.
Keywords: mHealth; Telemanipulation; Telemedicine; Telerobotics; Video Compression; Wireless Video Transmission